Semiochemicals and microbial antagonists: their role in integrated pest management in Latin America - Hilje, Luko (CATIE, Turrialba (Costa Rica) IFS, Estocolmo (Suecia), 2014)
Ilus. Tab. Bib. También en disco compacto